Representation of Medical Content in Online Discourse - I. I. Torubarova (Дискурс)
Introduction. The article discusses issues of representing medical information in online communities. Much attention is paid to modern areas of research on network discourse. Particular emphasis is paid to studies related to the problems of the terminology of the area. In this regard, the article presents different points of view on the typology and classification of texts in Internet-mediated communication. The area of interest for this study is medical content presented in Internet-mediated communication. The work specifies the concept of “medical content”. Methodology and sources. A study corpus is formed in accordance with the aim – to analyse the features of presenting medical information in English-language online discourse; methods of analysis are determined depending on the aim. The following criteria are used to analyse the study corpus material: pragmatic, media, structural-semantic and stylistic-linguistic parameters. The research corpus includes texts published in English, presented on the Reddit website within communities discussing issues of healthy lifestyle, health care, and pathological conditions. Results and discussion. Based on pragmatic parameters (type of addressee/type of addresser) and the topic of published information, the research material can be conditionally divided into several groups, the description of each group is given in the paper. The results obtained allow suggesting that medical content within the online community is aimed at two main population groups - healthcare professionals and lay people who are interested in issues related to the medical area. The medical information is presented based on a pragmatic and thematic principle. In terms of pragmatics, the main functions of presenting medical information are informative, ascertaining, phatic, expressive. Conclusion. The content of the research corpus consists of verbal texts with varying degrees of creolization – zero, partial, complete. They are characterised by all the features of the oral and written language typical of Internet-mediated communication.